1008 Incidental Solitary Cystic Mediastinal Lymphangioma with Mass Effect Complications: A Case Report. (12th October 2021) - Youssef, S; Iftikhar, S; Haris, M; Sundararajan, S; Abid, Q
Abstract: Introduction: Cystic mediastinal lymphangiomas (CML) are exceedingly rare, representing <1% of cystic lymphangiomas (CL), and typically present before 2 years of age. Few cases describe adult presentations of solitary CML and none describe symptomatic cases with 'mass-effect' complications. We describe an incidental finding of a symptomatic solitary CML causing mass effect complications and our definitive surgical management. Case Report: A 44-year-old Caucasian male presented with reduced responsiveness due to mixed drug overdose of fluoxetine and ibuprofen. Plain chest radiograph (CXR) revealed incidental new mediastinal widening. Thoracic computed tomography (CT) showed a well-defined lesion (75x63mm) in the right paratracheal region, with associated compression of the superior vena cava, left brachiocephalic vein and displacement of the azygos vein. Further questioning revealed 6-months history of non-productive cough, worsening dyspnoea on exertion and chest pain radiating to the right of the chest. Complete surgical resection was performed via posterolateral thoracotomy. It was seen compressing the 2 nd and 3 rd intercostal nerves. Enlarged lymph nodes at station 4 and 10 were excised and sent for analysis with aspirate from the excised lesion. Pathological gross examination showed a multiloculated cystic lesion containing thin straw-coloured fluid. Microscopically, it was thin walled with smooth muscle and scattered clusters of lymphocytes; its lining was markedly attenuated comprising bland flat endothelial cells, positive for CD-31. Lymph node samples showed reactive changes. Conclusions: Although CMLs are benign, their location and growth in the mediastinum can result in compression of surrounding structures. Early detection and complete surgical resection are paramount to prevent such complications and lesion recurrence.